Legal reform for rectifying child violence in educational settings through the lens of justice - Mashdurohatun, Anis; Sopiah, Euis; Harris, Muhammad; Radot, Porman Patuan; Mulia, Jhon (Edelweiss Applied Science and Technology, 2025)
Child violence in educational settings is a pressing issue that demands urgent legal reform to ensure the safety and well-being of both students and academics. This article examines the current legal frameworks addressing child violence in schools and advocates for reform based on the principles of justice. It critically analyzes the existing regulations, including the Law on Child Protection and the Law on Teachers and Lecturers, highlighting their limitations in effectively preventing and addressing incidents of violence. The article argues that while these laws provide some degree of protection for children, they often fail to strike a balance between safeguarding students and ensuring the fair treatment of academics, who are sometimes unjustly penalized for enforcing discipline. By focusing on justice-based values, the article proposes a reconceptualization of existing legal provisions, incorporating clearer guidelines that protect children from various forms of violence—physical, psychological, and sexual—while also safeguarding the rights of academics. The proposed legal reforms emphasize the importance of defining the boundaries of disciplinary actions in educational settings, ensuring that academics are not criminalized for maintaining order. Furthermore, the article stresses the need for continuous professional development programs for teachers, aimed at enhancing conflict resolution skills and preventing abusive behaviors. Ultimately, the article calls for a more equitable and just legal system that addresses the complexities of child violence in schools, ensuring that both children and academics are protected in a way that promotes a safe and productive learning environment. The proposed reforms have the potential to reshape the educational landscape, fostering a culture of respect, understanding, and accountability.